2020
DOI: 10.5334/ijic.4718
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Among Structures, Team Processes, and Outcomes for Service Users in Quebec Mental Health Service Networks

Abstract: Background: Few studies have identified and compared profiles of mental health service networks (MHSN) in terms of structures, processes, and outcomes, based on cluster analyses and perceptions of team managers, MH professionals and service users. This study assessed these associations in Quebec metropolitan, urban and semi-urban MHSN. Methods: A framework adapted from the Donabedian model guided data management, and cluster analyses were used to identify categories. Study participants included team managers (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 95 publications
1
3
0
Order By: Relevance
“…This finding is consistent with literature suggesting that dimensions of Relational Coordination increased shared accountability and support among team members across numerous business sectors and settings (Bolton et al, 2021). Feeling supported is essential in mental health teams because the work can often be challenging (Fleury et al, 2020). Moreover, participants noted that having mutual respect and shared goals of prioritizing patient care enabled team members to cover for one another within their scope of practice, which in turn, improved provider job satisfaction.…”
Section: Practice Implicationssupporting
confidence: 85%
See 2 more Smart Citations
“…This finding is consistent with literature suggesting that dimensions of Relational Coordination increased shared accountability and support among team members across numerous business sectors and settings (Bolton et al, 2021). Feeling supported is essential in mental health teams because the work can often be challenging (Fleury et al, 2020). Moreover, participants noted that having mutual respect and shared goals of prioritizing patient care enabled team members to cover for one another within their scope of practice, which in turn, improved provider job satisfaction.…”
Section: Practice Implicationssupporting
confidence: 85%
“…Healthcare is interdisciplinary, requiring professionals from different training backgrounds and specialties to work alongside one another. Ample research has shown that team functioning in integrated healthcare teams affects the quality and safety of patient care and reduces healthcare service fragmentation (Fleury et al, 2020;Manser, 2009;Schmutz & Manser, 2013). Teamwork is an especially important component of mental health services, as many patients present with complex medical and psychosocial needs, which may require providers from psychiatry, psychology, social work, nursing, and pharmacology, among others (Kinnair, Anderson, van Diepen, & Poysey, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wait times to access MH-PCT and psychiatric care are also quite long, varying from several months to more than a year especially for psychiatric care in some Quebec territories [67,82]. Benchmarks originally set for access to treatment were 1-month for MH-PCT and evaluations within 7-days were promoted for the one-stop MH service teams [65], yet these standards have to be met due to organizational issues and high patient demand [67,68,83].…”
Section: Study Contextmentioning
confidence: 99%